2022
DOI: 10.1088/1361-648x/aca579
|View full text |Cite
|
Sign up to set email alerts
|

On the photovoltaic effect asymmetry in ferroelectrics

Abstract: Despite symmetrical polarization, the magnitude of a light-induced voltage is known to be asymmetric with respect to poling sign in many photovoltaic (PV) ferroelectrics (FEs). This asymmetry remains unclear and is often attributed to extrinsic effects. We show here for the first time that such an asymmetry can be intrinsic, steaming from the superposition of asymmetries of internal FE bias and electro-piezo-strictive deformation. This hypothesis is confirmed by the observed decrease of PV asymmetry for smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 84 publications
2
12
0
Order By: Relevance
“…It was shown that the PV effect asymmetry is connected with the internal field and should be explained by the superposition of the electric bias and electro-piezo-strictive deformation. [11] At the same time, our data testify that annealing allows to compensate considerably the internal field and asymmetry of the PV effect that is very important for the reproducibility of the PV properties. In contrast, the sample annealing is followed by a pronounced enhancement of its PV response by nearly 20% for the applied subcoercive voltage of 2.7 kV cm À1 regardless of the sign of poling.…”
Section: Influence Of Annealing On the Fe And Pv Propertiessupporting
confidence: 57%
See 2 more Smart Citations
“…It was shown that the PV effect asymmetry is connected with the internal field and should be explained by the superposition of the electric bias and electro-piezo-strictive deformation. [11] At the same time, our data testify that annealing allows to compensate considerably the internal field and asymmetry of the PV effect that is very important for the reproducibility of the PV properties. In contrast, the sample annealing is followed by a pronounced enhancement of its PV response by nearly 20% for the applied subcoercive voltage of 2.7 kV cm À1 regardless of the sign of poling.…”
Section: Influence Of Annealing On the Fe And Pv Propertiessupporting
confidence: 57%
“…[ 11 ] These conclusions were independently confirmed by the computer modeling data as well as by the experiments revealing a remarkable sensitivity of the polarization and the resulting PV amplitude to the influence of external pressure. [ 11 ] On the basis of these data, one can suggest that the asymmetric P – E loop as well as PV response, first of all, would be explained by the influence of tensions arising during the process of crystal growth. Due to the piezoelectric effect, they cause the asymmetry of the domain structure: the polarizations of the opposite signs corresponding to the different groups of domains do not fully compensate each other.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Optical Neuromorphic Function. As multiple different polarization states exist in FEs in the subcoercive region, 38 the electric ground state was defined and stabilized in a reproducible way prior to optical excitations. To this end, the structure was electrically poled in darkness to reach the remanent FE state noted as point 1 in Figure 1c,d.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The last one is much faster and can be used to create reconfigurable neuromorphic-like system patterns. Moreover, taking into account that the PV effect in FE can be nonsymmetric with respect to poling sign 38 (i.e., different PV responses at remanent FE states 1 and 2 due FE bias and stresses), one can program the multicell behavior, as shown in Figure 6. The light pulse of the same energy can depress one artificial synapse while potentiating another at the given FE ground state, enabling a higher density of neural integration.…”
Section: ■ Discussionmentioning
confidence: 99%